"A New Reconstructive Method after Pancreaticoduodenectomy: the Triple Roux on a "P" Loop. Rationale and Radionuclide Scanning Evaluatlon.". Issue 4 (1996) - Pescio, Gianluigi; Cariati, Erminio
Abstract : We propose a method of reconstruction after pancreaticoduodenectomy consisting of a double Roux en Y on the same jejunal loop without interruption of the mesentery and a third anatomical Roux en Y to reconstitute the alimentary tract. The construction of the double Roux en Y draining pancreas and bile ducts separately, requires a linear Stapler 3-4 centimeters from the biliary anastomosis. In this way, by employing the same loop without mesenteric interruption, two functional excluded loops will be 'obtained. The rationale of the suggested model is based on the separation of biliary and pancreatic secretions. This makes it possible to avoid a stagnant cul-de-sac coinciding with the pancreaticojejunal anastomosis and to obtain in the case of leakage, a pure biliary and/or pancreatic fistula as far as is possible. 99mTc HIDA scans demonstrated the efficiency, of the biliopancreatic limbs of the reconstruction, showing normal emptying time for the gastric remnant and the absence of radionuclide stagnation or any alkaline enterogastric reflux.